Educating Financial Accounting: A Need Analysis for Technology-Driven Problem-Solving Skills - Hettiarachchi, Nuwan Lakmal; Subramaniam, Tamil Selvan; Muhammad Nurtanto, Muhammad Nurtanto; Sarala Thulasi Palpanadan, Sarala Thulasi Palpanadan; Zachariah John A. Belmonte, Zachariah John A. Belmonte; Arul Lawrence Antony Selvaraj,, Arul Lawrence Antony Selvaraj,; Nur Kholifah, Nur Kholifah (2022)
The teaching and learning process of financial accounting (FA) has become a challenge in an ever-changing global perspective, and an important discussion is replacing classroom teaching with career-based requirements. Problem-solving skills (PSS) help determine the source of problems and find appropriate solutions in teaching FA topics. This study aimed to identify the need for problem-solving skills for FA students for job readiness and identify the appropriate technology-savvy platform to improve problem-solving skills. Undergraduate students at the College of Banking and Financial Studies (CBFS) in Muscat, Sultanate of Oman, were selected as the research domain for data collection and analysis. This study reports a part of a preliminary study conducted using a survey technique on FA students. The main finding was that they had placed problem-solving skills as one of the important job skills in the modern financial accounting era. Furthermore, the needs analysis reflected the importance of the quiz-based learning (QBL) method embedded in Microsoft Forms (MFS) as a technology-based platform for teaching and learning about FA. Therefore, this study collected findings from the needs analysis phase with the help of QBL-MFS to improve the problem-solving skills of FA students to prepare them with life skills to be applied in the world place.